(untitled) (Global Journal of Human-Social Science, 2021)
The modern-day Nigerian society is well known for diverse of crises mainly among the major religious groups within the society. Such conflicts are usually orchestrated either by religious sects or ethnic activists who claimed that the government has not been fair to them for whatever reasons. The present day Nigeria is convulsing in disorders and violent religious crises. Wars and violent deaths are most daily occurrences in every nook and cranny of the nation. There have been reported loss of lives and wanton destruction of properties. Schools and businesses are being shot down, foreign investors no longer see Nigeria as a place to invest peacefully. Socially, politically and morally, the nation is in turmoil. Hardly can one speak of progress when the systems failed to maintain at least a minimum level of social decorum. The fact that Nigerians can no longer live together in peace is obvious. Religious and political conflicts have blinded us. Christians in particular are becoming desperate and angry, as there is no abating of these conflicts, and as the stark reality is dawning on those who live on the frontlines of the conflict that it is just a matter of when and where the next religious conflict will occur.